2019
DOI: 10.1002/stc.2443
|View full text |Cite
|
Sign up to set email alerts
|

Shake table tests and numerical investigation of a resilient damping device for seismic response control of building structures

Abstract: In this study, shake table tests of a multistory steel frame structure designed according to Eurocodes 3 and 8 with and without the newly developed prestressed viscous damper (PVD) have been carried out at the Institute of Earthquake Engineering and Engineering Seismology in Macedonia. An array of strong ground motion records has been applied to the reduced-scale test structure to assess the efficiency and seismic performance of the equipped building with PVDs. It has been revealed that with the implementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Experimental research on the damped structures can be conducted using pseudo-static tests [26]. Alternatively, a more direct approach is to utilize a seismic simulation shaking table for dynamic testing [27,28]. Nevertheless, there have been only a few shaking table tests that have specifically focused on the damped structure with additional viscous dampers and the non-damped structure without any additional viscous dampers.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental research on the damped structures can be conducted using pseudo-static tests [26]. Alternatively, a more direct approach is to utilize a seismic simulation shaking table for dynamic testing [27,28]. Nevertheless, there have been only a few shaking table tests that have specifically focused on the damped structure with additional viscous dampers and the non-damped structure without any additional viscous dampers.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have also conducted research on the impact of viscous damping on low-rise reinforced concrete frame structures under earthquakes, compared the seismic evaluation of RC buildings with and without friction dampers, and studied the impact of friction damping isolation systems on the performance of prefabricated concrete buildings [5][6][7]. Through continuous research by scholars, various types of dampers have emerged, including a new type of seismic damper based on the yielding of cantilever metal components proposed by TS Ahn and other scholars [8], a magnetorheological (MR) grease damper proposed by T. Sakurai and other scholars [9], and a prestressed viscous damper (PVD) proposed by A Bogdanovic and other scholars [10].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that frames equipped with SBPB and PBSC performed better than frames equipped with BRB. Bogdanovic et al [20] evaluated steel structures with and without prestressed viscous dampers. The results showed that using this damper, the structural responses are reduced by 10 to 70% .…”
Section: Introductionmentioning
confidence: 99%